Early recurrence of macular schisis in X-linked retinoschisis treated with vitrectomy for rhegmatogenous retinal detachment under silicone oil: case report and brief literature review - Panagiotis Stavrakas; Foteini Tsapardoni; Efthymios Karmiris; Ioannis Iatropoulos; Konstantinos Kounas; Spyridon Lygeros; Vassilios Kozobolis; Demetrios G. Vavvas (Therapeutic Advances in Ophthalmology, 2024)
X-linked retinoschisis (XLRS) is an inherited retinal degeneration affecting males, characterized by splitting of the retinal layers. We herein present the outcomes of surgical treatment in a case of XLRS complicated by rhegmatogenous retinal detachment (RRD). A 22-year-old male presented to the emergency department due to decreased visual acuity and visual field defect in his left eye Oculus Sinister (OS) of 1 week duration. The patient reported an early onset retinal degeneration and decreased visual acuity in both eyes since childhood in his past ocular history. Upon presentation, best corrected visual acuity (BCVA) was 6/30 on the right eye Oculus Dexter (OD) and 6/120 OS. Fundus examination revealed areas of peripheral retinal schisis, and the characteristic spoke wheel pattern on the macula of both eyes. In OS, a temporal RRD involving the macula was identified. The patient underwent surgical treatment with pars plana vitrectomy with internal limiting membrane (ILM) peeling, endolaser, and silicone oil (SO) tamponade. BCVA in OS improved to 6/60 and schistic cavities resolution was observed in the immediate postoperative period. The patient’s BCVA further improved to 6/19 at 1 month, as foveal anatomy showed relative improvement. However, there was a rapid reappearance of schisis spaces in the macular area at this point, which was also followed by progressive deterioration of foveal schisis by 3 months post-operatively. The resorption and recurrence of lamellar macular schisis changes after ILM peel and presence of SO, highlights that although XLRS findings can temporarily improve upon surgical intervention, the pathogenetic mechanisms contributing to disease phenotype remain to be elucidated.